Brasil: da identidade à marca - Maria Celeste Mira (Ciências Sociais Unisinos)
Throughout our history, the idea of Brazil has been the subject of several elaborations, in general combining political and aesthetic aspects. However, at the turn of the third mil- lennium this process has taken a new shape. Appropriations and reworkings of the idea of Brazil multiplied. The initiatives were everywhere, reaching different sectors of cultural and artistic production, the media and especially the market. The objective of this paper is to present the results of a documentary research project on the topic conducted in the course of the 2000s, which indicate two basic changes in comparison to the movements in the 20 th century: the displacement of political interest to marketing, as well as of the emphasis on national identity to cultural diversity. In conclusion, we discuss the implica- tions of the slide of identity construction from the sphere of politics to consumption.